KONSTRUKSI PEMANEN AIR HUJAN (RAIN WATER HARVESTING) UNTUK MEMENUHI KEBUTUHAN AIR DOMESTIK DI DESA PRANCAK KECAMATAN PASONGSONGAN KABUPATEN SUMENEP - Rohman, Khoirur Rohman; Rahmanto, Ach Desmantri (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
Prancak Village, Pasongsongan District is a village with a population of 6,693 people with a detailed population of 3,377 men, while 3,316 women, consisting of 8 hamlets. Tegal Barat Hamlet is experiencing a shortage of clean water due to the difficulty of springs and the absence of PDAM and clean water services from the government, so that when they experience a shortage of clean water, the people of Prancak Village take clean water to the spring in West Lebeng Village. The aim of this research is to find out how to plan the construction of Rain Water Harvesting and the Rain Water Harvesting distribution system in Tegal Barat Hamlet, Prancak Village. This research uses data collection methods in the form of observation, interviews, literature study, hydrological methods, hydraulics methods, rainwater harvester construction planning, and Epanet 2.0 data input. Based on the calculation results, the total area of ​​the rainwater catchment area (house roof) is 14191.505 m2 with the storage capacity obtained from the first block 127 m3, the second block 122 m3, the third block 94 m3, the fourth block 215 m3, the fifth block 174 m3, the sixth block 324 m3, the seventh block is 408 m3, the eighth block is 484 m3 so that it is able to meet the clean water needs in West Tegal Hamlet amounting to 77% of the total clean water. The distribution of clean water uses the transmission distribution method with pumps and the distribution uses a gravity system with a total pipe length of 1096 meters, for a 2-½'' inch diameter pipe length of 364 meters, a diameter of 60 mm or 2'' pipe length of 732 meters.